MEDICATION ADHERENCE AND STRESS LEVELS IN RELATION TO QUALITY OF LIFE AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS - Putri Cahyaningrum; Rif'atul Fani; Mokhtar Jamil (Poltekkes Kemenkes Jakarta III, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic disease that may affect physical, psychological, and social well-being, thereby influencing patients’ quality of life. This study aimed to analyze the relationship between medication adherence and stress levels with quality of life among patients with T2DM in primary healthcare. A quantitative analytical observational study with a cross-sectional approach was conducted among 83 patients with T2DM selected using purposive sampling. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), stress levels using the Perceived Stress Scale (PSS-10), and quality of life using the Diabetes Quality of Life–Brief Clinical Inventory (DQoL-BCI). Data were analyzed using Chi-square tests with a significance level of p ≤ 0.05. Most respondents demonstrated high medication adherence (47.0%), low stress levels (47.0%), and high quality of life (48.2%). There was a significant relationship between medication adherence and quality of life (p = 0.005). Respondents with higher medication adherence tended to report better quality of life. Stress level was also significantly associated with quality of life (p = 0.032), where higher stress levels were associated with poorer quality of life. Medication adherence and stress levels were significantly associated with quality of life among patients with T2DM. These findings highlight the importance of integrating adherence support and psychosocial management into diabetes care in primary healthcare settings.